KEPENTINGAN INDONESIA MENGIMPOR TELUR AYAM DARI AMERIKA SERIKAT - Yolanda, Mutia; ', Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The increase in egg prices was triggered by the high price of local chicken feed. Then the government imports eggs on the grounds that the price of imported eggs is cheaper than local chicken eggs. It needs to be underlined by the government to limit the entry of egg imports so that local breeds of chickens do not accumulate, rot and farmers do not lose money. Even though the quality of local breed eggs is the same as eggs outside research in this writing is in the form of descriptive analysis, which is a method that serves to describe or describe the object under study through data or samples that have been collected as they are without conducting analysis and making conclusions that apply to the public. In other words, analytical descriptive research takes problems or focuses attention on problems as they are when the research is carried out, the results of the research are then processed and analyzed to draw conclusions. Indonesia in 2018 carried out a policy of importing eggs originating from the United States. This policy is taken based on several interests, which are as follow: First, the import of eggs is carried out to secure supply. National chicken egg production experienced a surplus in 2018-2019, however, the surplus figure was still relatively small. So the government imports eggs. Second, egg imports are carried out because egg prices continue to soar. The government took the decision to increase the import quota because the price of chicken eggs was still high. The development of purebred chicken egg prices at the consumer level per month for the 2017-2018 period fluctuated and tended to increase. Third, egg imports are carried out to prevent transmission of the avian influenza virus (Avian Influenza AI). Imports in the form of eggs are expected to prevent the transmission of avian influenza (AI). This is because imports in the form of live chickens have the potential to be contaminated with AI while transiting in a country, and fourth, eggs are a priority product of the Ministry of Trade's Strategic Plan (Renstra). Keywords: Indonesia, Import, Eggs, United States